The Evolving Story in the Genetic Analysis for Heart Failure - Miyazawa, Kazuo; Ito, Kaoru (Frontiers in Cardiovascular Medicine, 2021)
Genomic studies of cardiovascular diseases have achieved great success, not only in Mendelian genetic diseases such as hereditary arrhythmias and cardiomyopathies, but also in common diseases such as ischemic heart disease and atrial fibrillation. However, only limited success has been achieved in heart failure due to the complexity of its disease background. In this paper, we will review the genetic research for heart failure to date and discuss how we can discover new aspects of heart failure from the viewpoint of genomic perspective.